2016
DOI: 10.1039/c5cp07766d
|View full text |Cite
|
Sign up to set email alerts
|

Predicting 17O NMR chemical shifts of polyoxometalates using density functional theory

Abstract: We have investigated the computation of (17)O NMR chemical shifts of a wide range of polyoxometalates using density functional theory. The effects of basis sets and exchange-correlation functionals are explored, and whereas pure DFT functionals generally predict the chemical shifts of terminal oxygen sites quite well, hybrid functionals are required for the prediction of accurate chemical shifts in conjunction with linear regression. By using PBE0/def2-tzvp//PBE0/cc-pvtz(H-Ar), lanl2dz(K-) we have computed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 60 publications
2
10
0
Order By: Relevance
“…The exchange-correlation approximation also hardly affects the Mn-O bonds, by 2-3 pm on average. Our findings agree with those of earlier studies on POMs [17,18] where similarly small variations of structure parameters had been determined for different exchange-correlation functionals. This similarity did not carry over to calculated chemical shifts [18] and energies of frontier molecular orbitals [17].…”
Section: Structural Parameters Of the Neutral Oxide Moietysupporting
confidence: 93%
See 4 more Smart Citations
“…The exchange-correlation approximation also hardly affects the Mn-O bonds, by 2-3 pm on average. Our findings agree with those of earlier studies on POMs [17,18] where similarly small variations of structure parameters had been determined for different exchange-correlation functionals. This similarity did not carry over to calculated chemical shifts [18] and energies of frontier molecular orbitals [17].…”
Section: Structural Parameters Of the Neutral Oxide Moietysupporting
confidence: 93%
“…Previous studies found that experimental structural parameters of Keggin-type polyoxometalates are best reproduced in PBE0 calculations [17,18]. However, the average absolute errors of the functionals PBE0, B3LYP, and PBE, do not exceed 3 pm [17,18]. In conclusion, calculations with GGA and various hybrid func-tionals yield rather similar structural parameters, in contrast to the resulting energy characteristics [17,18].…”
Section: Structural Parameters Of the Neutral Oxide Moietymentioning
confidence: 57%
See 3 more Smart Citations